Donald Trump meets Carl Schmitt. (December 2019) - Scheuerman, William E.
By revisiting late-Weimar debates between Carl Schmitt and two left-wing critics, Otto Kirchheimer and Franz L Neumann, we can shed light on the surprising alliance of populist politics with key tenets of economic liberalism, an alliance that vividly manifests itself in the political figure and retrograde policies of Donald Trump. In the process, we can begin to fill a striking lacuna in recent scholarly literature on populism, namely its failure to pay proper attention to matters of political economy. We can also perhaps begin to make sense of the roots of Trump's assault on the US federal state: formal law and its organizational basis, modern bureaucracy, represent potential restraints on the alliance of populism with neoliberalism.